2003
DOI: 10.1097/00005768-200301000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Exercise, the Valsalva Maneuver, and Cerebrovascular Transmural Pressure

Abstract: Unilateral bicep curl RE results in a greater increase in CVTMP compared to a VM performed alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 7 publications
0
56
0
6
Order By: Relevance
“…This can happen when forceable exhalation occurs against a closed glottis (a Valsalva manoeuvre), for example during coughing or defecation, but also while blowing into high resistance instruments, such as a saxophone. Non-invasive measurements have identified a rise in intraocular pressure in such musicians, reflecting increased intravenous pressure 2 3. Our patient was playing his saxaphone for several hours a night prior to admission.…”
Section: Discussionmentioning
confidence: 75%
“…This can happen when forceable exhalation occurs against a closed glottis (a Valsalva manoeuvre), for example during coughing or defecation, but also while blowing into high resistance instruments, such as a saxophone. Non-invasive measurements have identified a rise in intraocular pressure in such musicians, reflecting increased intravenous pressure 2 3. Our patient was playing his saxaphone for several hours a night prior to admission.…”
Section: Discussionmentioning
confidence: 75%
“…In fact, cerebral blood volume can increase only if cerebrospinal fluid volume decreases (total volume of the cranium cannot change); however, both central venous pressure and central spinal fluid pressure are increased during the maneuver (22,24,33). A number of studies, employing BL-based NIRS, report increased cerebral blood volume and oxygenation during VM (34,36,49).…”
Section: Vmmentioning
confidence: 99%
“…3 Recent studies also showed that cerebrospinal fluid pressure and ICP increased during the VM in patients after neurosurgical operations. 4,11 In addition, central venous pressure and internal jugular venous pressure increased to the same extent as intrathoracic pressure, which approximates the expiratory pressure during the VM. [1][2][3]10 Of note, the magnitude of changes in intrathoracic pressure during the VM did not change after autonomic blockade.…”
Section: Study Limitationsmentioning
confidence: 99%
“…1,3 Valsalva maneuvers are performed both voluntarily and involuntarily during daily life under many conditions such as coughing, defecation, and heavy weightlifting. 1,4 Associated with different levels of expiratory strain, intrathoracic pressure may increase from only a few to Ͼ150 mm Hg in healthy subjects. 1 Such large increases in intrathoracic pressure alter the systemic and cerebral circulations dramatically and could precipitate cerebral catastrophes.…”
mentioning
confidence: 99%